2010
DOI: 10.1590/s0066-782x2010005000140
|View full text |Cite
|
Sign up to set email alerts
|

Varfarina ou Aspirina na prevenção de fenômenos embólicos na valvopatia mitral com fibrilação atrial

Abstract: Background: Atrial fibrillation (AF) associated to rheumatic mitral valve disease (RMVD) increases the incidence of thromboembolism (TE), with warfarin being the standard therapy, in spite of difficulties in treatment adherence and therapeutic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…And claim that this has a low early and late mortality, a high survival free of complications and low need for reoperation. Lavitola et al19 compared the effectiveness of Aspirin vs. Warfarin in thromboembolism prevention in patients with Atrial fibrilation and claim that in patients presenting fibrillation for less than a year and no previous embolism, aspirin is little effective. However, in patients with lower-risk mitral valvulopathy (mitral regurgitation and mitral biological prosthesis), especially in cases presenting contraindication to or low adherence to warfarin, aspirin use can present some benefit in thromboembolism prevention.…”
Section: Introductionmentioning
confidence: 99%
“…And claim that this has a low early and late mortality, a high survival free of complications and low need for reoperation. Lavitola et al19 compared the effectiveness of Aspirin vs. Warfarin in thromboembolism prevention in patients with Atrial fibrilation and claim that in patients presenting fibrillation for less than a year and no previous embolism, aspirin is little effective. However, in patients with lower-risk mitral valvulopathy (mitral regurgitation and mitral biological prosthesis), especially in cases presenting contraindication to or low adherence to warfarin, aspirin use can present some benefit in thromboembolism prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Characteristics of the 8 trials are summarized in Tables 1 and 2 . With the exception of the studies by Lavitola et al 27 and Hu et al, 34 participants in the studies were >70 years of age, and the ages of the participants were generally similar between the treatment arms. The number of participants in the anticoagulant treatment arms ranged from 36 to 555 (n = 2169), whereas the number in the antiplatelet treatment arms ranged from 39 to 545 (n = 2194).…”
Section: Resultsmentioning
confidence: 89%
“… 26 Thus, 9 articles met the inclusion criteria and were included in the analysis. 7 , 27 – 34 Two of the articles report findings of the Stroke Prevention in AF II study. 31 , 32 However, because each article presented unique data, both were included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For Lavitola et al [ 4 ] in certain situations, in patients with mitral bioprosthesis in the presence of atrial fibrillation, where is commonly indicated prophylaxis with oral anticoagulants, the replacement of the anticoagulant by aspirin could be considered. However, for mechanical prostheses, continuous oral administration of antivitamin K would always be indispensable, with or without concomitant atrial fibrillation.…”
Section: Introductionmentioning
confidence: 99%